Fragmentada: o constante fluxo de construção, desconstrução e reconstrução do corpo que dança - Maivald, Ana Caroline Bazzo (2020)
The present work is presented in the simple report form and it details the creative process of a videodance, that results from a study carried out with the ballet technique and with researches through improvisation movement in dance. The organization and execution of this research happens in social isolation due to the covid-19 pandemic. Therefore, it developed in individual production. For this construction and composition of artistic work, a careful look is given to the body in dance trajectory until now.